Recent Developments in the Use of Intralesional Injections Keloid Treatment - Aurelia Trisliana Perdanasari; Davide Lazzeri; Weijie Su; Wenjing Xi; Zhang Zheng; Li Ke; Peiru Min; Shaoqing Feng; Yi Xin Zhang; Paolo Persichetti (Archives of Plastic Surgery, 2014)
Keloid scars are often considered aesthetically unattractive and frustrating problems that occur following injuries. They cause functional and cosmetic deformities, displeasure, itching, pain, and psychological stress and possibly affect joint movement. The combination of these factors ultimately results in a compromised quality of life and diminished functional performance. Various methods have been implemented to improve keloid scars using both surgical and non-surgical approaches. However, it has proven to be a challenge to identify a universal treatment that can deliver optimal results for all types of scars. Through a PubMed search, we explored most of the literature that is available about the intralesional injection treatment of hypertrophic scars and keloids and highlights both current (corticosteroid, 5-fluorouracil, bleomycin, interferon, cryotherapy and verapamil) and future treatments (interleukin-10 and botulinum toxin type A). The reference lists of retrieved articles were also analysed. Information was gathered about the mechanism of each injection treatment, its benefits and associated adverse reactions, and possible strategies to address adverse reactions to provide reliable guidelines for determining the optimal treatment for particular types of keloid scars. This article will benefit practitioners by outlining evidence-based treatment strategies using intralesional injections for patients with hypertrophic scars and keloids.